Direct Patterning of Oriented Metal-Organic Framework Crystals via Control over Crystallization Kinetics in Clear Precursor Solutions - Ameloot, Rob; Gobechiya, Elena; Uji-i, Hiroshi; Martens, Johan A.; Hofkens, Johan; Alaerts, Luc; Sels, Bert F.; De Vos, Dirk E. (Advanced materials (Weinheim), 2010)
Processing metal–organic frameworks with spatial and temporal control over crystal formation will increase the applicability of these highly porous materials. By exploiting solvent effects, stable synthesis solutions can be obtained, which can be used in combination with soft lithographic techniques to deposit oriented crystals in patterns by in situ crystallization (see figure).